PLATELET INDICES AND DIABETIC NEPHROPATHY SEVERITY IN TYPE 2 DIABETES MELLITUS - Barabde, Wrishikesh M. (Journal of Biomedical and Pharmaceutical Research, 2021)
BACKGROUND: Diabetes Mellitus is a chronic metabolic disorder that affects the entire world's population, with rates increasing in Asia and peaking in the Indian subcontinent. Indians are more susceptible to type 2 diabetes due to a genetic tendency to insulin resistance, which results in high incidence of DM; that is why India is known as the "Diabetes Capital of the World". Type 2 diabetes mellitus (T2DM) is characterised by insulin resistance in body tissues and impaired insulin excretion by the pancreas. Diabetes results in long-term diabetes-related complications in multiple organ systems due to persistent hyperglycemia and metabolic dysregulation. These complications cause the bulk of morbidity and mortality associated with the disease, reducing the patient's quality of life and imposing large financial costs on the patient, family, and healthcare system.AIM: Correlation of platelet indices with severity of diabetic nephropathy in type 2 diabetes mellitus.MATERIAL AND METHOD: This was an Observational cross-sectional study performed. All patients of T2DM visiting OPD as well as getting admitted in the department of medicine were selected randomly and screened for nephropathy. And only the patients developing nephropathy were considered as the study population Informed consent was secured from the patients for participation in the study.  At the same time, Venous samples were also drawn for the evaluation of fasting blood sugar, HbA1C, serum creatinine and other routine investigations like serum Urea, serum electrolytes and liver function tests. CBC which includes haemoglobin, thrombocyte counts, Platelet indices like MPV, PCT, PDW, P-LCR; were assessed by the device – Sysmex XN 1000 automated hematology analyser.RESULTS: In all patients of diabetes, developing nephropathy, anemia is more prevalent and it occurs early in the course of development of complication.  Association of hypertension in diabetes patients, increases the risk of developing microvascular complications. Platelet indices like MPV, PDW, PCT, PLCR are significantly raised in all diabetic patients developing nephropathy. As well when associated with other microvascular complications like retinopathy and neuropathy, MPV and PDW are found to be elevated.  The platelet indices correlated with the progression of nephropathy stages. MPV, PDW, PLCR and PCT were significantly higher as there was increase in severity of nephropathy.CONCLUSION: Thus, changes in platelet indices are found to be statistically associated with diabetes and its microvascular complications and being cost effective, noninvasive and being easily available in peripheral blood counts; these platelet indices can be used as a surrogate marker to predict the presence and the progression of diabetic nephropathy much earlier in life, as well, MPV and PDW can be also used as marker for the presence of other microvascular complications of diabetes.KEYWORDS: Microvascular, Diabetic nephropathy, Diabetes mellitus and Platelet Indices